2017
DOI: 10.1111/acem.13107
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing Systemic Corticosteroid Treatments to Mitigate Relapse in Adults With Acute Asthma: A Systematic Review and Network Meta‐analysis

Abstract: The network analysis identified IM corticosteroids and PO long-course corticosteroids as the most effective strategies to prevent relapse among adults with acute asthma, compared to PO short-course corticosteroids. The lack of significant findings with PO short-course corticosteroids is likely due to the paucity of research. Further comparative studies are required to determine the safety and effectiveness of briefer PO SCS treatment options in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Despite the heterogeneity of the trials, subsequent systematic reviews have concurred that there is no convincing difference in clinical outcomes between higher or lower doses of prednisolone, nor duration of use of prednisolone, nor whether a tapering of dose was used. [42][43][44] A study comparing 2 days of dexamethasone with 5 days of prednisone showed similar rates of relapse and time to return to normal activity suggesting the former strategy may be an option. 45 Caution is required in anyone taking dexamethasone for more than 2 days given its potent metabolic (diabetogenic) effects.…”
Section: What Dose Of Ocs?mentioning
confidence: 99%
“…Despite the heterogeneity of the trials, subsequent systematic reviews have concurred that there is no convincing difference in clinical outcomes between higher or lower doses of prednisolone, nor duration of use of prednisolone, nor whether a tapering of dose was used. [42][43][44] A study comparing 2 days of dexamethasone with 5 days of prednisone showed similar rates of relapse and time to return to normal activity suggesting the former strategy may be an option. 45 Caution is required in anyone taking dexamethasone for more than 2 days given its potent metabolic (diabetogenic) effects.…”
Section: What Dose Of Ocs?mentioning
confidence: 99%
“…Similarly, in adults, systemic steroids reduced acute relapse rates, though the course of prednisone needed to be at least 7-10 days in duration, with shorter courses being ineffective (65). Treatment with ICS cannot be used in place of OCS (66), but may prevent the need to use OCS in acute asthma.…”
Section: Adjusting Ics/ocsmentioning
confidence: 99%
“…The clinical features of asthma resulting from reversible airway inflammation include chest tightness, worsening cough, shortness of breath, and wheezing [1]. In our context, most patients managed for acute exacerbation of asthma respond favourably to treatment with standard management protocol [2]. Systemic and oral steroids are administered, followed by gradual resolution of symptoms.…”
Section: Introductionmentioning
confidence: 99%